Chinese manufacturing performance in comparative perspective, 1980-2002 - Adam Szirmai; Ruoen Ren; Manyin Bai (Yale University, Economic Growth Center, 2005)
This paper uses the detailed information in the 1995 Census of Industrial Production as a benchmark for analysing the coverage, concepts and consistency of published statistical series. On the basis of the analysis, the paper proposes a series of adjustments which result in more consistent long-run series of labour productivity for 21 manufacturing sectors from 1980-2002. For purposes of international comparisons with the USA, the paper subsequently presents industry of origin unit value ratios for the benchmark year 1995. These are used to convert Chinese value added into US dollars. In 2002, value added for the statistically well-covered sectors of Chinese manufacturing was 43 per cent of US value added, against 12 per cent in 1980. The comparative analysis of labour productivity points to a long period of Chinese growth without catch up from 1980-1992. After 1992, there was a rapid and accelerating process of catch up. In comparative terms labour productivity increased from 5.3 per cent of the US level in 1995 to 13.7 per cent in 2002.
Keywords: O14; O40; O47; 330; China; manufacturing; productivity growth; catch up; unit value ratios; internationalcomparisons